2013
DOI: 10.1182/blood-2012-07-443457
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes assemble podosomes that degrade matrix and protrude through basement membrane

Abstract: • Murine and human megakaryocytes assemble podosomes.• Megakaryocyte podosomes remodel matrix.Megakaryocytes give rise to platelets via extension of proplatelet arms, which are released through the vascular sinusoids into the bloodstream. Megakaryocytes and their precursors undergo varying interactions with the extracellular environment in the bone marrow during their maturation and positioning in the vascular niche. We demonstrate that podosomes are abundant in primary murine megakaryocytes adherent on multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(144 citation statements)
references
References 49 publications
(76 reference statements)
4
136
1
3
Order By: Relevance
“…In MKs, the Arp2/3 complex has previously been shown to play a role in both DMS formation and podosome formation. 49,50 However, to our knowledge, the direct role of Arp2/3 phosphorylation in proplatelet formation has not been studied. Interestingly, podosome formation by MKs has recently been proposed as a mechanism by which MKs degrade matrix and, in turn, cross basement membranes and release proplatelets into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…In MKs, the Arp2/3 complex has previously been shown to play a role in both DMS formation and podosome formation. 49,50 However, to our knowledge, the direct role of Arp2/3 phosphorylation in proplatelet formation has not been studied. Interestingly, podosome formation by MKs has recently been proposed as a mechanism by which MKs degrade matrix and, in turn, cross basement membranes and release proplatelets into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…1D). These linear invadosomes are formed along type I collagen fibrils and are found in both normal and transformed cells (Di Martino et al, 2015;Juin et al, 2012;Juin et al, 2014;Schachtner et al, 2013). Linear invadosomes present markers that are common to all invadosomes, such as the actin-binding proteins N-WASP and cortactin (Artym et al, 2006), the scaffold protein tyrosine kinase substrate 5 (Tks5, also known as SH3PXD2A) (Blouw et al, 2015) and the Rho GTPase Cdc42 (Di .…”
Section: Induction Of Invadosome Formationmentioning
confidence: 99%
“…For instance, a recent study has demonstrated that cells from the metastatic breast cancer line MDA-MB 231 preferentially form integrin-dependent actin dots on a high density of fibrillar collagen, which corresponds to compressed and fixed collagen I (Artym et al, 2015). Several other studies have demonstrated that cells preferentially form linear actin structures on fibrillar collagen I (Monteiro et al, 2013;Schachtner et al, 2013). Based on these findings, we propose that the resulting invadosome architecture might depend less on the particular cell type than on the experimental setting used for their observation.…”
Section: Invadosome Plasticitymentioning
confidence: 99%
“…Stage V and VI account for cells displaying proplatelet extensions. In stage V, during the initial stages of proplatelet extension the MK starts to spread and its cytoplasm unravels into cytoplasmic extensions, called podosomes [23]. As the cytoplasmic erosion continues, the extensions elongate and are remodeled into thinner strands with a pearl-on-a-string morphology, which will eventually shed into platelets [24].…”
Section: In Vitro Label Free Evaluation Of Megakaryocytic Developmentmentioning
confidence: 99%